Russian Idea, Jewish Presence Essays on Russian-Jewish Intellectual Life - Horowitz, Brian (Academic Studies Press, 2013)
In Russian Idea--Jewish Presence, Professor Brian Horowitz follows the career paths of Jewish intellectuals, who, having fallen in love with Russian culture, were unceremoniously repulsed by outsiders. Horowitz relays the paradoxes of a synthetic Jewish and Russian self-consciousness in order to correct critics who have always considered Russians and Jews to be polar opposites and even enemies. In fact, the best Russian Jewish intellectuals Semyon Dubnov, Maxim Vinaver, Mikhail Gershenzon, and a number of Zionist writers and thinkers were actually inspired by Russian culture and attempted to develop a sui generis Jewish creativity in three languages on Russian soil.
Description based on print version record.
KU Open Services
Keywords: History / Russia & The Former Soviet Union; History; Electronic books